Advanced Infant Scale: Function Enhancement by Integrating a Monitoring Application for Growth and Development Assessment - Prameswari Diahasna Tsany -; Husneni Mukhtar; Willy Anugrah Cahyadi (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
StuVent is an application designed to provide information on the health status of infants aged 0-24 months and to detect early stunting. This application displays the classification results of the infant's health status, differentiated by colour, making it easier for users to understand the infant's health status. StuVent is aimed at Posyandu's staff and the general public to help them detect early stunting. The main advantage of this application is its ability to work offline using Bluetooth Low Energy (BLE) connectivity. Users can connect their smartphones to the scales via Bluetooth, allowing the application to be used without an internet connection. This feature is particularly beneficial for users in 3T areas (frontier, outermost and remote regions) where internet access is often limited. StuVent is therefore expected to be an effective tool for monitoring child growth and preventing stunting in various regions.